Title of the Integrity Analysis of O&G Standpipe Separator: Numerical Study Article - Faizal Hakim Hidzir, Mohd; Imran Sainan, Khairul; Husain, Hazran (International Journal of Engineering and Technology, 2018)
A standpipe is a component that functions to remove the condensate of gas from the oil that flows inside the O&G piping system underneath. Efficient gas removal promotes better crude oil quality and increases productivity. The deflector plates integrity in a stand pipe, where thin plates are mounted on the pipe walls periodically in the direction of fluid flow, has been numerically investigated. Â The aim of this investigation is to determine how the working fluid density and deflectors thickness influenced the plates integrity. Two working fluids were tested. Natural gas and crude oil which has a higher density. The thickness of the plates was 3 mm and 6 mm. A series of simulation analyses were done analytically through CFD and FEA simulation method using ANSYS software. Based on the results, crude oil produces higher stress onto the plates. This causes large plate deflection. It was observed, the plates near to the standpipe inlet were subjected to the highest stress. Stress on the deflector plates drops as the fluid travel along the pipe height. The deflector plates of 3 mm were failed under these conditions and were not recommended for usage.Â